Are medium cut-off membranes the future, or the promising reality for chronic hemodialysis patients? - Noemí Del Toro-Cisneros; Erick Y. Zuñiga-González; Adrián E. Caballero-Islas; José A. Geraldo-Murillo; Mauricio Arvizu-Hernández; Olynka Vega-Vega (Permanyer, 2023)
The development of hemodialysis (HD) membranes has substantially advanced in the last decade. This has resulted in the manufacturing of medium cut-off membranes (MCO) whose internal architecture is based on greater pore size and a smaller diameter, thus promoting the clearance of particles of greater size as well as retrofiltration. Multiple studies have proven their efficacy in the clearance of uremic mid-sized molecules such as B2-microglobulin, free light chains, and some interleukins; this clearance is far superior with MCO membranes when compared with high-flux HD, and similar to that obtained with online hemodiafiltration. This review summarizes the results of the most relevant clinical studies of this membrane in terms of uremic toxin clearance, as well as the features of some clinical outcomes such as quality of life and hospitalizations.